SAT-714 Cadmium, an Endocrine Disruptor of the Reproductive Axis in Mice - Fiordelisio, Tatiana (J Endocr Soc, 2020)
Endocrine disruptors, are chemicals that can alter organism endocrine system. Within these, the heavy metal cadmium is one of the most toxic industrial and environmental metals. Neuroendocrine system act in precise amounts and moments in time, disturbances caused by endocrine disruptors are suspected to be implicated in the recent declining fertility. The effect of cadmium, intraperitoneally injected, on the intracellular calcium activity of gonadotropes was evaluated in an ex vivo preparation of the entire pituitary gland of male BalbC mice by calcium imagenology techniques. In preliminary results, an increase in baseline intracellular calcium activity was observed, as well as an increase in the number of gonadotropes that respond to a GnRH and express gonadotropins. In addition, a change in the pattern of response to GnRH was observed, the biphasic type response being predominant, and an oscillatory depolarization of greater intensity and duration in response to KCl, which is not affected by nifedipine. The results allow us to infer that cadmium affects the function of pituitary gonadotropes and thus probably fertility.